Differences in nickel ions released from nickel-titanium arch wire after immersion in detergent and non-detergent toothpaste - Hilda Fitria Lubis; Kholidina Imanda Harahap; Nadia Tamari Lubis (Majalah Kedokteran Gigi Indonesia, 2020)
Nickel-titanium (NiTi) arch wire has properties that favor its use during the leveling and aligning phase of orthodontic treatment. This NiTi orthodontic arch wire has the potential to experience nickel ion release. One factor that can cause the release of nickel ions is toothpaste. Nickel ions released can enter the body and cause carcinogenic, mutagenic, cytotoxic, and allergic effects. The purpose of this study was to see the differences of nickel ions released from NiTi orthodontic arch wire after immersion in detergent and non-detergent toothpaste. This was a laboratory experimental research to draft a comparative design. The sample size was 40 pieces of NiTi orthodontic arch wire which were divided into 2 groups, immersion in detergent toothpaste and immersion in non-detergent toothpaste. The sample used was NiTi arch wire solution immersed in toothpaste and distilled water for 24 hours in an incubator at 37 °C then measured using inductively coupled plasma (ICP) mass spectrometer to determine the released nickel ions. Data were analyzed usingMann-Whitney test. The Mann-Whitney test resulted in a value of 0.872 (p≥0.05) which indicates no significant difference between the two groups. The study concluded that there is no difference in the nickel ions released from NiTi orthodonticarchwire after immersion in detergent and non-detergent toothpaste.